Community perceptions of gender-based violence: the role of strategic communication and digital health in prevention and recovery - Gloria Nnadwa Alhassan; Felicia Bodi Alhassan (Aposta: Revista de Ciencias Sociales, 2026)
Gender-based violence (GBV) is a pervasive but under-documented problem in sub-Saharan Africa, with little community-level evidence from mid-sized Nigerian towns. This study examined community perceptions of the nature, causes, effects, and preferred solutions to GBV in Suleja Local Government Area, Niger State, Nigeria, and considered whether strategic communication, social media, and digital health tools could extend locally-preferred prevention and recovery strategies. A concurrent mixed-methods design combined a structured questionnaire administered to 120 community members with a focus group discussion involving five survivors and two service providers. Descriptive statistics and weighted mean scoring ranked perceived causes and effects, while transcripts were analysed thematically. Most respondents (85.8%) reported direct or witnessed GBV, and 62.5% rated it a very serious problem. Poverty was the most endorsed cause, followed by low education and childhood exposure to violence, while psychological trauma, fear, and suicidal ideation were the most endorsed effects. Awareness campaigns were the most preferred intervention (79.2%), ahead of legal or law-enforcement measures, consistent with the behaviour change literature. The study also considers digital health tools, including teletherapy, chatbot helplines, and mobile safety planning, as a low-cost complement to recovery services, and outlines steps needed to test these strategies causally in similar Nigerian settings.